Physiological activities and yield of yacon potato are affected by soil water availability - Mendes Tiago P.; da Silva Josimar A.; Avelar Felipe V. R.; dos Reis Edvaldo F.; Cavatte Paulo C.; de Oliveira Fábio L. (Open Agriculture)
The commercial cultivation of yacon is relatively new, creating several knowledge demands regarding its agricultural management, including water relations. Thus, the aim of this study is to understand the effects of different soil water availability levels on the physiological activities of yacon. The first experiment aimed to establish the survival limit of the plants under water deficit, while the second aimed to determine the range for optimal development within a smaller range of water availability. A completely randomized design was adopted, with four replications and five treatments (soil water tension levels). The first experiment used tensions of 30, 60, 100, 200, and 300 kPa, while the second used tensions of 20, 30, 45, 60, and 75 kPa. Evaluations included net CO2 assimilation rate, stomatal conductance, transpiration rate, intercellular CO2 concentration, chlorophyll indices, nitrogen balance, anthocyanin, and flavonoid content. The yacon’s survival limit under water deficit occurred at 200 kPa, when the plant reached the lowest assimilation rate (11.607 µmol CO2 m−2 s−1), representing a 57.53% reduction in its photosynthetic capacity before dying under the 300 kPa tension. From 100 kPa tension, flavonoid production increased, indicating that yacon plants activated defense mechanisms to mitigate the effects of water stress. The highest photosynthetic rates in yacon were observed under higher water availability (lower tension, 20 kPa), close to the soil’s field capacity (10 kPa). In the first experiment, significant tuberous root production was observed only at 30 kPa, yielding approximately 1,100 g plant−1. In the other treatments, fresh tuberous root production was around 100 g plant−1, but without meeting commercial standards (small and very thin roots). In the second experiment, a linear decrease in production was observed as soil water availability declined. Overall, the production ranged from 1156.3 to 135.2 g plant−1, between the highest and lowest water availability levels applied (tensions of 20 and 75 kPa, respectively), with a 16.05% reduction in yield for every 10 kPa increase in soil water tension. This result has the practical implication of demonstrating that yacon potato exhibits better physiological performance, and therefore the potential for higher productivity, when soil water availability is close to field capacity. This is a fundamental and guiding piece of information for irrigation management in yacon cultivation.